2016
DOI: 10.2147/ott.s98203
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA GAS5 is a critical regulator of metastasis phenotype of melanoma cells and inhibits tumor growth in vivo

Abstract: The present study intended to demonstrate the effects of long noncoding RNA growth arrest-specific transcript 5 (GAS5) on the migration and invasion of melanoma cells. We first detected the expression of GAS5 among four kinds of melanoma cell lines, followed by constructing GAS5-knocked down and overexpressed stable cells. Next, we evaluated the effects of GAS5 on cell migration and invasion using wound healing and gelatin zymography assays. Finally, melanoma cells with different GAS5 expression were injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 71 publications
1
46
0
1
Order By: Relevance
“…Furthermore, it has been shown that demethylation of the MMP9 promoter region can facilitate MMP9 expression, which may be an essential factor in the occurrence and progression of DN . In our study, we discovered an inverse relationship between GAS5 and MMP9 expression, which is partially consistent with findings in a previous study that the gelatinolytic activity of MMP9 in melanoma cells was increased by siRNA‐mediated silencing of GAS5 . Furthermore, our study suggested that GAS5 was capable of recruiting EZH2 to the promoter region of MMP9, which drive H3K27me3, thus leading to downregulated MMP9 expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, it has been shown that demethylation of the MMP9 promoter region can facilitate MMP9 expression, which may be an essential factor in the occurrence and progression of DN . In our study, we discovered an inverse relationship between GAS5 and MMP9 expression, which is partially consistent with findings in a previous study that the gelatinolytic activity of MMP9 in melanoma cells was increased by siRNA‐mediated silencing of GAS5 . Furthermore, our study suggested that GAS5 was capable of recruiting EZH2 to the promoter region of MMP9, which drive H3K27me3, thus leading to downregulated MMP9 expression.…”
Section: Discussionsupporting
confidence: 91%
“…30 In our study, we discovered an inverse relationship between GAS5 and MMP9 expression, which is partially consistent with findings in a previous study that the gelatinolytic activity of MMP9 in melanoma cells was increased by siRNA-mediated silencing of GAS5. 31 Furthermore, our study suggested that GAS5 was capable of recruiting EZH2 to the promoter region of MMP9, which drive H3K27me3, thus leading to downregulated MMP9 expression. EZH2, a component of PRC2, is a histone H3K27 methyltransferase and plays a critical role in gene expression regulated by lncRNAs.…”
Section: Discussionmentioning
confidence: 70%
“…The current progress in the treatment of melanoma mainly remained focused on exploring the function of the immune system as well as the oncogenic driver mutations in melanoma [21]. Previous evidence has indicated the role of lncRNA GAS5 in the progression of melanoma, which could be the possible indicators for melanoma and could serve as a therapeutic target [22]. EZH2 [23], as well as CDKN1C [24], have also been recognized as promising biomarkers for treating melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…These etiologies are associated with varying clinical outcomes18 and affect chromosomes or protein-coding genes. The dysregulation of lncRNA expression has been linked to various diseases1920212223. However, studies of the roles of lncRNAs in neuroblastoma are lacking.…”
Section: Discussionmentioning
confidence: 99%